Does influenza pandemic preparedness and mitigation require gain‐of‐function research? - Adam, Dillon C. (Influenza Other Respir Viruses, 2017)
The risk and benefits of gain‐of‐function studies on influenza A have been widely debated since 2012 when the methods to create two respiratory transmissible H5N1 mutant isolates were published. Opponents of gain‐of‐function studies argue the biosecurity risk is unacceptable, while proponents cite potential uses for pandemic surveillance, preparedness and mitigation. In this commentary, we provide an overview of the background and applications of gain‐of‐function research and argue that the anticipated benefits have yet to materialize while the significant risks remain.